Green areas and their impact on the carbon footprint A study of the relationship between vegetation cover and emissions in Al-Kut city - Alwan, Maitham; خليفة, ندى (Journal of Planner and Development, 2026)
Abstract: This study aims to analyze and demonstrate the environmental role of green spaces, particularly in reducing the carbon footprint in the city of Al-Kut, by evaluating the relationship between vegetation cover and greenhouse gas emissions resulting from urban activities. The importance of the study lies in highlighting the environmental potential of green areas as natural and effective tools for absorbing carbon dioxide and improving air quality, especially in light of rapid urban expansion and increasing climatic pressures facing Iraqi cities.. Remote sensing data were utilized through the Google Earth Engine platform to calculate the Gross Primary Productivity (GPP) and the Normalized Difference Vegetation Index (NDVI) during the period from 2003 to 2023, and to analyze the spatial and temporal changes in vegetation carbon absorption efficiency. Additionally, the carbon footprint of the city for the year 2023 was calculated using the IPCC methodology and emission factors related to energy and fuel consumption. The results revealed  that the improvement in NDVI and GPP indices over the past two decades positively reflected the environmental absorption efficiency, despite increasing urbanization pressures. The study showed that the total carbon dioxide emissions in Al-Kut city for the year 2023 exceeded 1,184,290 tons of CO₂-equivalent, while the amount of carbon absorbed by vegetation was estimated at approximately 469,693 tons, highlighting a major environmental gap that necessitates effective planning interventions.. It also recommends adopting vegetation carbon indicators in local planning policies